Pengaruh Dana Pihak Ketiga dan Financing to Deposit Ratio terhadap Return on Asset Bank Aceh Syariah pada Tahun 2018 – 2022 - Maya Lestari; Fitria Mandaraira (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2025)
This study aims to examine the effect of Third Party Funds (TPF) and Financing to Deposit Ratio (FDR) on Return on Asset (ROA) of Bank Aceh Syariah. The analysis was conducted using monthly time series data published by Bank Aceh Syariah in a study period from 2018 to 2022. This study uses a quantitative causality approach. Data analysis was conducted using multiple linear regression. Hypothesis testing was conducted using statistical tests, namely partial tests (t-test) and simultaneous tests (F-test). The results of the study showed that TPF and FDR together had a positive and significant effect on ROA. Partially, TPF has a positive and significant effect on ROA, while FDR has a positive but insignificant effect on ROA.